Preparation method of magnesium alloy corrosion-resistant thermal control coating

Through CNC laser texture and microarc oxidation treatment, combined with nano copper oxide treated with irradiation modification, a magnesium alloy corrosion-resistant thermal control coating is formed, which solves the problem that magnesium alloy coatings have both corrosion resistance and thermal control properties in the prior art, and achieves efficient corrosion resistance and thermal control performance on the surface of magnesium alloy.

CN119913588AActive Publication Date: 2025-05-02NORTHEASTERN UNIV CHINA

Patent Information

Application Number
CN202510412322.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-05-02
Estimated Expiration
2045-04-03

AI Technical Summary

Technical Problem

In the prior art, there are few researches on the coating of magnesium alloys that have both corrosion resistance and thermal control, and it is difficult to effectively improve the corrosion resistance and thermal control properties of magnesium alloys.

Method used

The oxide film on the surface of the magnesium alloy was removed by CNC laser texture treatment, and then the magnesium alloy after CNC laser texture treatment was used as the anode to perform microarc oxidation treatment, and nanocopper oxide treated with irradiation modified as the electrolyte additive to form a microarc oxidation coating.

Benefits of technology

The activity and roughness of the surface of magnesium alloy is improved through laser texture treatment, and nanoparticles are encouraged to be incorporated into the coating during microarc oxidation, which improves the thermal control performance and corrosion resistance of the coating, significantly reduces the porosity of the coating, and enhances the hydrophobicity and wear resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913588A_ABST
    Figure CN119913588A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a magnesium alloy corrosion-resistant thermal control coating, and relates to the technical field of metal surface treatment. The preparation method comprises the following steps: carrying out numerical control laser texturing treatment on the surface of the magnesium alloy with an oxide film removed; the magnesium alloy subjected to numerical control laser texturing treatment serves as an anode, micro-arc oxidation treatment is conducted, and a micro-arc oxidation coating is formed on the surface of the magnesium alloy so as to improve the corrosion resistance and thermal control performance of the magnesium alloy; wherein the electrolyte additive is nano copper oxide subjected to irradiation modification treatment. According to the method, the magnesium alloy surface is subjected to laser texturing treatment, so that more regular and ordered holes are formed in the magnesium alloy surface, the activity and roughness of the magnesium alloy surface are improved, on one hand, the thermal control performance of the micro-arc oxidation coating is improved, and on the other hand, the microstructure uniformity of the micro-arc oxidation coating is improved; the porosity of the micro-arc oxidation coating is remarkably reduced, and the corrosion resistance of the micro-arc oxidation coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal surface treatment, and in particular to a method for preparing a magnesium alloy corrosion-resistant thermal control coating. Background Art

[0002] As the lightest structural metal material, magnesium alloy has good machinability, ductility, casting ability and good electromagnetic shielding characteristics. However, compared with other traditional metal materials, magnesium alloy has poor corrosion resistance. Therefore, improving the corrosion resistance of magnesium alloy is an urgent challenge to promote the application of magnesium alloy. In addition, in recent years, the application of thermal control coating technology in aerospace, electronic communications and automobile manufacturing has become increasingly widespread, and the research on thermal control properties of magnesium alloy has gradually become a hot topic.

[0003] In the prior art, there are few studies on magnesium alloy coatings with both corrosion resistance and thermal control properties. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art or related art.

[0005] To this end, the present invention provides a method for preparing a magnesium alloy corrosion-resistant thermal control coating, comprising: Perform CNC laser texturing on the surface of magnesium alloy with oxide film removed; The magnesium alloy treated by CNC laser texturing is used as the anode to perform micro-arc oxidation treatment to form a micro-arc oxidation coating on the surface of the magnesium alloy to improve the corrosion resistance and thermal control properties of the magnesium alloy; The electrolyte additive for micro-arc oxidation treatment is nano copper oxide modified by irradiation; the nano copper oxide modified by irradiation has a particle size of 50 nm to 700 nm and an addition concentration in the electrolyte of 5 g / L to 20 g / L.

[0006] Furthermore, the CNC laser texturing process comprises: A laser texturing pattern is designed, a processing path and a processing process of the numerically controlled laser texturing treatment are generated, and then the numerically controlled laser texturing treatment is performed using a laser galvanometer scanning method.

[0007] Furthermore, the laser galvanometer scanning has a galvanometer frequency of 9000 Hz to 12000 Hz, a laser power of 50 W to 200 W, a laser scanning speed of 5 mm / s to 20 mm / s, and a laser pulse frequency of 15 Hz to 30 Hz.

[0008] Furthermore, the micro-arc oxidation treatment includes: the magnesium alloy after CNC laser texturing treatment is used as the anode; the graphite plate is used as the cathode; the electrolyte is: NaF 5 g / L~7 g / L, Na2SiO3 25 g / L~35 g / L, NaOH 4 g / L~6 g / L, and the solvent is deionized water.

[0009] Furthermore, the irradiation modification treatment includes: the irradiation source is 6 MeV / u~8 MeV / u Bi 32+ Ion beam, irradiation time is 900 s~1000 s, irradiation flux rate is 10 5 ion / (s·cm 2 ).

[0010] Furthermore, the nano copper oxide modified by radiation has a particle size of 50 nm to 100 nm, and its addition concentration in the electrolyte is 8 g / L to 12 g / L.

[0011] Furthermore, the micro-arc oxidation treatment uses a constant current control power supply with a current density range of 3 A / dm 2 ~5 A / dm 2 , the voltage range is 420 V~480 V, the frequency is 200 Hz~300 Hz, the duty cycle is 30%~40%, and the micro-arc oxidation time is 5min~30 min.

[0012] Furthermore, during the micro-arc oxidation treatment, the electrolyte is stirred at a speed of 200 r / min to 500 r / min, and the electrolyte temperature is cooled to below 40°C.

[0013] Compared with the prior art, the present invention has at least the following beneficial effects: The preparation method of the corrosion-resistant thermal control coating of the magnesium alloy provided by the present invention improves the activity and roughness of the surface of the magnesium alloy by laser texturing pretreatment, and the surface of the magnesium alloy after laser texturing treatment has more regular and orderly holes, which allows more nanoparticles to be incorporated into the coating during the micro-arc oxidation process, and can further improve the thermal control performance of the coating. In addition, the laser texturing treatment makes an orderly adjustment to the surface structure of the magnesium alloy, which on the one hand improves the growth rate of the micro-arc oxidation coating and reduces the energy consumed in the micro-arc oxidation process, and on the other hand improves the uniformity of the microstructure of the micro-arc oxidation coating and significantly reduces the porosity of the micro-arc oxidation coating. The coating has the advantages of hydrophobicity, low surface roughness, and excellent corrosion resistance and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The metallographic morphology of the magnesium alloy after being processed by different CNC laser texturing parameters provided in the embodiment of the present application; wherein, Figure 1 a is the metallographic morphology of the magnesium alloy with a galvanometer frequency of less than 9000 Hz provided in the embodiment of the present application; Figure 1 b is the metallographic morphology of the magnesium alloy with a galvanometer frequency of more than 12000 Hz provided in the embodiment of the present application; Figure 1 c is the metallographic morphology of the magnesium alloy with a laser power of less than 50W provided in the embodiment of the present application; Figure 1 d is the metallographic morphology of the magnesium alloy with laser power > 200W provided in the embodiment of the present application; Figure 1 e is the metallographic morphology of the magnesium alloy with a scanning speed of <5 mm / s provided in the embodiment of the present application; Figure 1 f is the metallographic morphology of the magnesium alloy with a scanning speed of >20 mm / s provided in the embodiment of the present application; Figure 1 g is the metallographic morphology of the magnesium alloy with a pulse frequency of less than 15 Hz provided in the embodiment of the present application; Figure 1 h is the metallographic morphology of the magnesium alloy with a pulse frequency of more than 30 Hz provided in the embodiment of the present application; Figure 1 i is the metallographic morphology of the magnesium alloy with the preferred experimental parameters provided in the embodiment of the present application; Figure 1 j is the second metallographic morphology of the magnesium alloy with the preferred experimental parameters provided in the embodiment of the present application.

[0015] Figure 2 The micro-arc oxidation boost curves provided for Example 1 and Comparative Example 4 of the present application.

[0016] Figure 3 The metallographic morphology of the magnesium alloy after laser remelting treatment in comparative example 1 of the present application and the metallographic morphology of the magnesium alloy after laser texturing treatment in comparative example 2 are shown.

[0017] Figure 4 This is a scanning electron microscope image of the surface morphology of the magnesium alloy corrosion-resistant thermal control coating provided in Example 1 of the present application.

[0018] Figure 5 This is a scanning electron microscope image of the surface morphology of the magnesium alloy corrosion-resistant thermal control coating provided in Comparative Examples 1-6 of the present application.

[0019] Figure 6 This is a graph of the absorptivity of the magnesium alloy corrosion-resistant thermal control coating provided in Example 1 and Comparative Examples 1-6 of the present application.

[0020] Figure 7 Emissivity diagram of the magnesium alloy corrosion-resistant thermal control coating provided in Example 1 and Comparative Examples 1-6 of the present application.

[0021] Figure 8 Contact angle diagram of magnesium alloy micro-arc oxidation coating provided for comparative examples 1-4 of the present application.

[0022] Fig. 9 This is a contact angle diagram of the magnesium alloy corrosion-resistant thermal control coating provided in Example 1 of the present application.

[0023] Fig.10 Impedance diagram of magnesium alloy micro-arc oxidation coating provided for comparative examples 1-4 of the present application.

[0024] Fig.11 This is the impedance diagram of the magnesium alloy corrosion-resistant thermal control coating provided in Example 1 of the present application. DETAILED DESCRIPTION

[0025] In order to better understand the above technical solution, the technical solution of the present invention is described in detail below through specific embodiments.

[0026] An embodiment of the present invention provides a method for preparing a magnesium alloy corrosion-resistant thermal control coating, comprising: Perform CNC laser texturing on the surface of magnesium alloy with oxide film removed; The magnesium alloy after CNC laser texturing is used as the anode, and micro-arc oxidation treatment is carried out to form a micro-arc oxidation coating on the surface of the magnesium alloy to improve the corrosion resistance and thermal control of the magnesium alloy; wherein, the electrolyte additive for the micro-arc oxidation treatment is nano-copper oxide that has been modified by irradiation.

[0027] The method for preparing the corrosion-resistant thermal control coating of magnesium alloy provided in the embodiment of the present invention is a method for preparing the corrosion-resistant thermal control coating of magnesium alloy based on laser texturing pretreatment assisted micro-arc oxidation technology. The laser texturing pretreatment improves the activity and roughness of the magnesium alloy surface. The surface of the magnesium alloy after laser texturing has more regular and orderly holes, which allows more nanoparticles to be incorporated into the coating during the micro-arc oxidation process, which can further improve the thermal control performance of the coating. In addition, the laser texturing treatment adjusts the surface structure of the magnesium alloy in an orderly manner. On the one hand, it improves the growth rate of the micro-arc oxidation coating and reduces the energy consumed in the micro-arc oxidation process. On the other hand, it improves the uniformity of the microstructure of the micro-arc oxidation coating and significantly reduces the porosity of the micro-arc oxidation coating. The coating has the advantages of hydrophobicity, low surface roughness, excellent corrosion resistance, and wear resistance.

[0028] In a feasible implementation, the CNC laser texturing process includes: A laser texturing pattern is designed, a processing path and a processing process of the numerically controlled laser texturing treatment are generated, and then the numerically controlled laser texturing treatment is performed using a laser galvanometer scanning method.

[0029] Specifically, the laser texturing pattern needs to be accurately designed first, and the geometric shape and size need to be designed using CAD software. The pattern can be selected from simple geometric shapes or patterns such as squares, circles, diamonds, and wavy lines. The area of ​​the diamonds and squares can be 30 square microns to 100 square microns. During the texturing process, ensure that the material surface is flat without obvious ups and downs or bumps. Then use CAM software to generate the processing path and process of CNC laser texturing, and then use the laser galvanometer scanning method to perform CNC laser texturing.

[0030] In a feasible implementation, the laser galvanometer scans, the galvanometer frequency is 9000 Hz~12000 Hz, the laser power is 50 W~200 W, the laser scanning speed is 5 mm / s~20 mm / s, and the laser pulse frequency is 15 Hz~30 Hz.

[0031] Specifically, if the frequency of the laser galvanometer is too high or too low, it will cause deviations in the positioning of the light beam. When the frequency of the galvanometer is too high, the high-frequency vibration may cause the position of the galvanometer to shift or become misaligned, affecting the accurate control and positioning of the light beam, resulting in deviations in the pattern. The unstable vibration of the low-frequency galvanometer will reduce the stability of the light beam, and the beam may shake or drift. The experiment found that, taking the laser texturing pattern designed as a diamond as an example, when the galvanometer frequency is less than 9000 Hz, the laser cannot produce a diamond according to the set pattern, and defects will occur during operation; when the galvanometer frequency is greater than 12000 Hz, there will be too many dots. In addition, when the laser power is less than 50 W, the laser will have defects, and some positions will have defects due to insufficient laser power; when the laser power is greater than 200 W, excessive ablation will occur. Excessive and low scanning speeds and pulse frequencies will also affect the preparation of graphics. The experimental results are listed in Tables 1 and Figure 1 a- Figure 1 As shown in j, it can be seen that Figure 1 a- Figure 1 h cannot effectively prepare diamond patterns. Figure 1 i and Figure 1 j effectively prepared the diamond pattern, which is the optimal experimental parameter.

[0032] Table 1

[0033] In a feasible implementation, the micro-arc oxidation treatment includes: a magnesium alloy treated by CNC laser texturing is used as an anode; a graphite plate is used as a cathode; the electrolyte is: NaF 5 g / L~7 g / L, Na2SiO3 25 g / L~35 g / L, NaOH 4 g / L~6 g / L, the solvent is deionized water, and the electrolyte additive is nano copper oxide treated by irradiation. Among them, the irradiation modification treatment includes: the irradiation source is Bi 6 MeV / u~8 MeV / u 32+ Ion beam, irradiation time is 900 s~1000 s, irradiation flux rate is 10 5 ion / (s·cm 2 ); The particle size of nano copper oxide is 50 nm to 700 nm, and the concentration added in the electrolyte is 5 g / L to 20 g / L. Preferably, the particle size of nano copper oxide is 50 nm to 100 nm, and the concentration added in the electrolyte is 8 g / L to 12 g / L.

[0034] Specifically, the thermal control performance of the micro-arc oxidation coating is improved by in-situ doping nanoparticles with different band gap energies into the micro-arc oxidation electrolyte. The surface of the magnesium alloy after CNC laser texturing has more regular and orderly holes, which allows more nanoparticles to be incorporated into the coating during the micro-arc oxidation process, which can further improve the thermal control performance of the coating. Nano-copper oxide is a semiconductor material and a narrow band gap semiconductor. Its band gap is approximately between 1.2 and 1.9 electron volts (eV). After irradiation, the band gap of nano-copper oxide drops to between 0.5 and 0.6 electron volts (eV), which is more suitable for absorbing light in the visible and near-infrared spectral ranges. The absorption usually starts from about 600 nm and continues in a longer wavelength range. The irradiated nano-copper oxide is more conducive to improving the thermal control performance of the coating. Previous researchers have not used irradiated nano-copper oxide particles as thermal control coating additives. The irradiated nano-CuO was used as an electrolyte additive, and the effects of the addition amount and particle size of the irradiated nano-CuO on the coating were investigated. Specifically, when the added concentration of irradiated modified nano-CuO is less than 5 g / L, the doping content on the coating surface will be significantly reduced, affecting the thermal control effect of the coating; when the added concentration of irradiated modified nano-CuO is greater than 20 g / L, too much irradiated modified nano-CuO in the solution will affect the conductivity of the electrolyte and the micro-arc oxidation film formation. In addition, excessive irradiated modified nano-CuO agglomerates on the surface of the substrate, causing burning on the coating surface; therefore, the preferred added concentration of irradiated modified nano-CuO in the electrolyte is 8 g / L~12 g / L. In addition, experiments were also carried out on the particle size selection of irradiated modified nano-CuO: irradiated modified nano-CuO with particle sizes of 50 nm-100 nm, 200 nm-300 nm and 600 nm-700 nm were selected respectively, and the purity was ≥99.9%, among which the irradiated modified nano-CuO with particle sizes of 50 nm-100 nm had better dispersibility in the solution; under the same micro-arc oxidation parameter conditions, through EDS surface scanning, it was found that when 10 g / L of irradiated modified nano-copper oxide with a particle size of 50 nm-100 nm was added to the electrolyte, the Cu element content on the coating surface was 9.2 at.%, when 10 g / L of irradiated modified nano-copper oxide with a particle size of 200 nm-300 nm was added to the electrolyte, the Cu element content on the coating surface was 6.1 at.%, and when 10 g / L of irradiated modified nano-copper oxide with a particle size of 600 nm-700 nm was added to the electrolyte, the Cu element content on the coating surface was 4.3 at.%. Therefore, it is preferred that the particle size of the nano copper oxide modified by irradiation is 50 nm to 100 nm.

[0035] The experiment investigated the effect of electrolyte composition (the solvent was deionized water) on the performance of magnesium alloy corrosion resistant thermal control coating. The micro-arc oxidation parameters were: voltage 450 V, current density 4 A / dm 2 , frequency 200 Hz, duty cycle 30%, micro-arc oxidation treatment 10 min. See Table 2 for details. It can be seen from Table 2 that the preferred electrolyte is: NaF 6 g / L, Na2SiO3 30 g / L, NaOH 5g / L, and the electrolyte additive is nano copper oxide modified by irradiation, with an addition amount of 10 g / L. At this time, the particles in the coating are uniformly doped, the coating is thicker, the sparks are uniform and dense during the film formation process, and the pore size of the coating surface is uniform.

[0036] Table 2

[0037] In a feasible embodiment, the micro-arc oxidation treatment uses a constant current control power supply with a current density range of 3A / dm 2 ~5 A / dm 2 , the voltage range is 420 V~480 V, the frequency is 200 Hz~300 Hz, the duty cycle is 30%~40%, and the micro-arc oxidation time is 5 min~30 min.

[0038] The experiment found that when the micro-arc oxidation voltage is less than 420 V, the coating thickness is low; when the voltage exceeds 480 V, the violent discharge will cause the pore size of the coating surface to increase; so the control voltage range is 420 V~480 V. The current density is less than 3 A / dm 2 When the current density is higher than 5 A / dm 2 When the current is too high, the coating surface tends to become loose and porous.

[0039] Specifically, the frequency and duty cycle of micro-arc oxidation usually need to be changed together. When the frequency is too high and the duty cycle is low, the energy during each pulse will be insufficient to maintain a sufficiently strong discharge process, affecting the formation efficiency and integrity of the coating. When the frequency is low and the duty cycle is high, the oxide layer will be incompletely formed and the quality will be reduced, affecting the wear resistance and corrosion resistance of the oxide film. When the frequency is too high and the duty cycle is too large, it will lead to excessive oxidation, making the oxide layer too coarse, increasing the surface roughness, and reducing the surface quality. The experiment of this application shows that the preferred micro-arc oxidation treatment has a frequency of 200 Hz~300Hz and a duty cycle of 30%~40%. In addition, the micro-arc oxidation time is too short, less than 5min, and the coating is too thin, resulting in a decrease in the amount of particle doping in the coating, affecting the thermal control and corrosion resistance of the coating. When the micro-arc oxidation time is greater than 30 min, the coating oxidation time is too long, resulting in a loose structure of the oxide layer and a decrease in quality, affecting the hardness, wear resistance and corrosion resistance of the oxide layer.

[0040] In a feasible implementation manner, during the micro-arc oxidation process, the electrolyte is stirred at a stirring speed of 200 r / min to 500 r / min, and the electrolyte temperature is cooled to below 40°C.

[0041] Specifically, stirring during micro-arc oxidation is to allow the irradiated modified nano-copper oxide particles to be better dispersed throughout the electrolyte. When the speed is lower than 200 r / min, due to the large weight of the particles, a large number of particles may be deposited at the bottom of the solution, and the particle concentration in the solution is reduced. When the speed is higher than 500 r / min, the particles cannot be adsorbed on the surface of the substrate during micro-arc oxidation due to the high speed, which affects the particle doping amount in the coating. When the electrolyte temperature is higher than 40 °C, the solution temperature is too high, which will affect the pH value and chemical reaction rate of the solution, resulting in incomplete formation or quality degradation of the oxide layer, and reducing the hardness and adhesion of the oxide layer.

[0042] Example 1 A method for preparing a corrosion-resistant thermal control coating of a magnesium alloy The specific steps are as follows: (1) Sample pretreatment: The magnesium alloy sample was cut into 40 mm × 40 mm × 5 mm size. The surface of the magnesium alloy substrate was polished with 240#, 400#, 600#, 800#, 1000#, and 2000# roughness water-abrasive paper in sequence until the surface of the magnesium alloy substrate was smooth and flat, then rinsed and dried with alcohol for later use.

[0043] (2) Laser texturing: The pretreated samples were subjected to CNC laser texturing using a galvanometer scan with a galvanometer frequency of 12,000 Hz, a laser power of 100 W, a scanning speed of 10 mm / s, and a pulse frequency of 20 Hz. The diamond shape was designed using AutoCAD software and then input into the laser machine for processing.

[0044] (3) Micro-arc oxidation treatment: The sample obtained after laser texturing was used as the anode and the graphite plate as the cathode. The micro-arc oxidation electrolyte was poured into the electrolytic cell and then micro-arc oxidation treatment was performed. The micro-arc oxidation power supply was controlled by constant current, and the power supply voltage was set to 450 V and the current density was 4 A / dm 2, frequency 200 Hz, duty cycle 30%, micro-arc oxidation treatment for 10 min, that is, a corrosion-resistant thermally controlled micro-arc oxidation coating was prepared on the surface of the magnesium alloy. Among them, the micro-arc oxidation electrolyte is: NaF 6 g / L, Na2SiO330g / L, NaOH 5 g / L, nano-CuO 10 g / L, and the solvent is deionized water (the particle size of nano-CuO modified by irradiation is 50nm~100 nm). During the preparation process, an electric control stirrer is installed in the electrolytic cell, the stirring speed is 400 r / min, and indirect cooling is performed in the electrolytic cell at the same time, and the cooling temperature is set to 25℃.

[0045] Comparative Example 1 Preparation method of magnesium alloy corrosion resistant thermal control coating The specific steps are as follows: (1) Sample pretreatment: Same as Example 1.

[0046] (2) Laser melting treatment: The pretreated samples were subjected to laser melting treatment with a laser power of 500 W, a scanning speed of 5 mm / s, and a pulse frequency of 30 Hz.

[0047] (3) Micro-arc oxidation treatment: same as in Example 1.

[0048] Comparative Example 2 Preparation method of magnesium alloy corrosion resistant thermal control coating The specific steps are as follows: (1) Sample pretreatment: Same as Example 1.

[0049] (2) Laser texturing: The pretreated samples were subjected to CNC laser texturing using a galvanometer scan with a galvanometer frequency of 15,000 Hz, a laser power of 200 W, a scanning speed of 5 mm / s, and a pulse frequency of 10 Hz. The diamond shape was designed using AutoCAD software and then input into the laser machine tool for processing.

[0050] (3) Micro-arc oxidation treatment: same as in Example 1.

[0051] Comparative Example 3 Preparation method of magnesium alloy corrosion resistant thermal control coating The specific steps are as follows: (1) Sample pretreatment: Same as Example 1.

[0052] (2) Laser texturing treatment: same as in Example 1.

[0053] (3) Micro-arc oxidation treatment: The difference from Example 1 is that the micro-arc oxidation electrolyte contains 15 g / L NaF, 40 g / L Na2SiO3, 10 g / L NaOH, and 10 g / L CuO.

[0054] Comparative Example 4 Preparation method of magnesium alloy corrosion resistant thermal control coating The specific steps are as follows: (1) Sample pretreatment: Same as Example 1.

[0055] (2) Micro-arc oxidation treatment: same as in Example 1.

[0056] Comparative Example 5 Preparation method of magnesium alloy corrosion resistant thermal control coating The specific steps are as follows: (1) Sample pretreatment: Same as Example 1.

[0057] (2) Simultaneous treatment of laser texturing and micro-arc oxidation: During the process of preparing the coating by micro-arc oxidation, the coating is simultaneously subjected to laser texturing treatment using a laser. The laser texturing treatment parameters are the same as those in Example 1, and the micro-arc oxidation parameters are the same as those in Example 1.

[0058] Comparative Example 6 Preparation method of magnesium alloy corrosion resistant thermal control coating The specific steps are as follows: (1) Sample pretreatment: Same as Example 1.

[0059] (2) Micro-arc oxidation treatment: The pretreated samples were directly subjected to micro-arc oxidation treatment, and the micro-arc oxidation treatment parameters were the same as those in Example 1.

[0060] (3) Laser texturing: The coating is treated with a laser, and the laser processing parameters are the same as those in Example 1.

[0061] Results and Discussion: Roughness and wear rate test of the embodiments and comparative examples: After preparation, the samples were rinsed with deionized water and dried, and the roughness of the samples was tested using the sj-310 roughness meter produced by Mitutoyo Co., Ltd. of Japan, and the wear rate of the samples was tested using the H2R-2M reciprocating friction tester produced by Lanzhou Zhongke Kaihua Technology Development Co., Ltd. The results are shown in Table 3. As can be seen from Table 3, after the CNC laser texturing treatment of Example 1, the roughness of the micro-arc oxidation coating was significantly reduced, while the roughness of the coatings of the several schemes provided in Comparative Examples 1-6 were all relatively high. The samples were tested using the H2R-2M reciprocating friction tester produced by Lanzhou Zhongke Kaihua Technology Development Co., Ltd., and it was found that the wear rate of the coating provided in Example 1 was lower. Since the coating of Example 1 is smoother and more CuO is doped in the coating, the coating is more wear-resistant.

[0062] Table 3 Roughness and wear rate of magnesium alloy samples prepared in Examples and Comparative Examples

[0063] In both Example 1 and Comparative Example 4, the micro-arc oxidation pressure rise curve is shown in Figure 2 After CNC laser texturing, the pressure rise of micro-arc oxidation is faster, which improves the growth rate of micro-arc oxidation coating and reduces the energy consumed in the micro-arc oxidation process; while when micro-arc oxidation is performed alone, the pressure rise is slower during the coating preparation process and consumes more energy. Example 1 The metallographic morphology of the magnesium alloy after CNC laser texturing is a regular rhombus ( Figure 1 i), while the laser remelted surface of Comparative Example 1 is a rough molten surface ( Figure 3 Comparative Example 1), Comparative Example 2 When the laser power and pulse frequency are increased, the laser pattern cannot be regular ( Figure 3 Comparative Example 2), the laser power is too high, resulting in a deeper laser ablation pit ( Figure 5 Comparative Example 2). Example 1 Magnesium alloy corrosion resistant thermal control coating based on laser texturing pre-treatment + micro-arc oxidation treatment ( Figure 4 ), whose surface porosity is relatively low, significantly lower than that of the micro-arc oxidation coating provided in Comparative Examples 1-6 ( Figure 5 ).from Figure 5 It can be seen that: in comparative example 1, laser remelting + micro-arc oxidation slightly improved the coating morphology; in comparative example 2, the coating of laser texturing + micro-arc oxidation had a higher surface porosity and larger pores due to the excessively high laser power and pulse frequency of laser texturing; in comparative example 3, after changing the formula of the micro-arc oxidation coating, due to the high content of fluoride and sodium hydroxide in the solution, a large number of cracks appeared on the surface of the coating, and the pores were the largest; comparative example 4 was a magnesium alloy micro-arc oxidation coating without pre-treatment, and a large number of micropores also existed on its surface, and the pore size was large; comparative example 5 was a coating prepared by combining laser treatment during the micro-arc oxidation process, and the coating surface porosity was relatively high, indicating that laser treatment during the micro-arc oxidation process could not affect the growth morphology of the coating. The main reason for the analysis was that diffuse reflection would occur when the laser was irradiated into the electrolyte, which seriously affected the laser efficiency; comparative example 6 was a micro-arc oxidation coating subjected to laser treatment, and the surface did not present a regular shape after treatment, and ablation occurred on the surface, but the pores of the coating were not effectively closed, and the coating porosity was relatively high.

[0064] from Figure 6 and Figure 7 It can be seen that the absorption rates of comparative examples 1-6 are 0.63, 0.57, 0.47, 0.41, 0.39 and 0.51, and the emissivity are 0.85, 0.84, 0.85, 0.85, 0.85, 0.84, respectively, while the absorption rate of Example 1 is 0.96, and the emissivity is 0.96, which indicates that the laser texturing pre-treatment + micro-arc oxidation treatment of Example 1 effectively improves the thermal control performance of the coating, and successfully prepares a high-absorption and high-emission thermal control coating.

[0065] from Figure 8 and Fig. 9It can be seen that since the surface porosity of the micro-arc oxidation coatings provided in Comparative Examples 1-4 is relatively high, the contact angle of the coatings is relatively low, showing hydrophilicity. However, the micro-arc oxidation coating provided in Example 1 is hydrophobic due to the reduced surface porosity, and the contact angle reaches 117°.

[0066] from Fig.10 and Fig.11 It can be seen that the impedance value of the magnesium alloy micro-arc oxidation coating by laser texturing + micro-arc oxidation in Example 1 is significantly improved compared with that in Comparative Examples 1-4, indicating that the preparation method of the magnesium alloy corrosion-resistant thermal control coating in Example 1 effectively improves the corrosion resistance of the coating.

[0067] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed. The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application. The above are only preferred implementation methods of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.

Claims

1. A method for preparing a corrosion-resistant thermal control coating of a magnesium alloy, characterized in that: include: Perform CNC laser texturing on the surface of magnesium alloy with oxide film removed; The magnesium alloy treated by CNC laser texturing is used as the anode to perform micro-arc oxidation treatment to form a micro-arc oxidation coating on the surface of the magnesium alloy to improve the corrosion resistance and thermal control properties of the magnesium alloy; The electrolyte additive for micro-arc oxidation treatment is nano copper oxide modified by irradiation; the nano copper oxide modified by irradiation has a particle size of 50 nm to 700 nm and an addition concentration in the electrolyte of 5 g / L to 20 g / L.

2. The method for preparing the corrosion-resistant thermal control coating of magnesium alloy according to claim 1, characterized in that: The CNC laser texturing process comprises: A laser texturing pattern is designed, a processing path and a processing process of the numerically controlled laser texturing treatment are generated, and then the numerically controlled laser texturing treatment is performed using a laser galvanometer scanning method.

3. The method for preparing the corrosion-resistant thermal control coating of magnesium alloy according to claim 2, characterized in that: The laser galvanometer scanning has a galvanometer frequency of 9000 Hz to 12000 Hz, a laser power of 50 W to 200 W, a laser scanning speed of 5 mm / s to 20 mm / s, and a laser pulse frequency of 15 Hz to 30 Hz.

4. The method for preparing the corrosion-resistant thermal control coating of magnesium alloy according to claim 1, characterized in that: The micro-arc oxidation treatment comprises: The magnesium alloy after CNC laser texturing is the anode; The graphite plate is the cathode; The electrolyte is: NaF 5 g / L~7 g / L, Na2SiO3 25 g / L~35 g / L, NaOH 4 g / L~6 g / L, and the solvent is deionized water.

5. The method for preparing the corrosion-resistant thermal control coating of magnesium alloy according to claim 1, characterized in that: The irradiation modification treatment includes: the irradiation source is 6 MeV / u~8 MeV / u Bi 32+ Ion beam, irradiation time is 900 s~1000 s, irradiation flux rate is 10 5 ion / (s·cm 2 ).

6. The method for preparing the corrosion-resistant thermal control coating of magnesium alloy according to claim 1, characterized in that: The nano copper oxide modified by radiation has a particle size of 50 nm to 100 nm and is added to the electrolyte at a concentration of 8 g / L to 12 g / L.

7. The method for preparing the corrosion-resistant thermal control coating of magnesium alloy according to any one of claims 4 to 6, characterized in that: The micro-arc oxidation treatment uses a constant current control power supply with a current density range of 3 A / dm 2 ~5 A / dm 2 , the voltage range is 420 V~480 V, the frequency is 200 Hz~300 Hz, the duty cycle is 30%~40%, and the micro-arc oxidation time is 5 min~30 min.

8. The method for preparing the corrosion-resistant thermal control coating of magnesium alloy according to claim 7, characterized in that: During the micro-arc oxidation treatment, the electrolyte is stirred at a speed of 200 r / min to 500 r / min, and the electrolyte temperature is cooled to below 40°C.

Citation Information

Patent Citations

  • Laser method for improving binding force of ceramic coating and metal matrix

    CN109112602A

  • Method for improving wear resistance and corrosion resistance of magnesium alloy

    CN111945148A

  • Method for improving corrosion resistance of magnesium alloy through synchronous combination of laser and micro-arc oxidation

    CN115433988A

Cited By

  • Magnesium alloy surface thermal control wear-resistant lubricating film layer and preparation method thereof

    CN120591741A